(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Larisa D. Bednarskaya (Orel, Russian Federation) Competence paradigm of education in the new regulatory documents is interpreted as system and activity based education. The wording of the meta-subject, subject and personal learning outcomes are presented in the form of universal education. Awareness of language consistency in the process of teaching allows to build linguistic systems to achieve optimal results in training, to organize level (individual) nature of learning activity in interactive, including computer, mode. Raster grid of regulatory, communicative and cognitive UEA completely overlaps with active individualized process of development of speech in all its forms. Key words: introduction in educational process of system-activity paradigm of education; wording of the regulatory UEA as the impetus to realize the consistency of the content of education and the creation of system-activity patterns of study. DOI 10.23683/1995-0640-2017-3-178-184